Breadlines Knee-Deep in Wheat: Food Assistance in the Great Depression - Janet Poppendieck (University of California Press, 2014)
"For the American farmer, 1932 was a year of singular misfortune," reported the New York Times on New Year's Day, 1933. Between January and mid December, average farm prices had fallen by more than 18 percent, following a drop of nearly 50 percent in the two previous years. Two days later, a more detailed report on farm prices predicted a continuation of the rock bottom levels: "The huge surpluses of leading agricultural products that have been accumulated during the last few years are expected generally to preclude more than a moderate recovery in prices in 1933, even if there should be a decided falling off in production." On the same day, according to another Times report, a leading New York social worker told a Senate committee that relief agencies were losing their battle to prevent starvation. "Deaths due to insufficient food have been reported in several cities," declared H. L. Lurie on behalf of the American Association of Social Workers, and he warned of possible violence by the unemployed if adequate relief measures were not taken.1 For many Americans, this juxtaposition of hunger and abundance had become a central symbol of the irrationality of the economic system. "A breadline knee-deep in wheat," noted commentator James Crowther, "is obviously the handiwork of foolish men."2 While oranges were being soaked with kerosene to prevent their consumption in California, whole communities in Appalachia were living on dandelions and wild greens. Corn was so cheap that it was being burned for fuel in county courthouses in Iowa, but large numbers of cows, sheep, and horses were starving to death in the drought-stricken Northwest. Dairies were pouring unsaleable milk down the sewers, while unemployed parents longed to provide even a pint a week for their growing children. In February 1932, Oklahoma union activist and editor Oscar Ameringer painted a vivid picture of this troubling contrast for a congressional committee. He joined a parade of witnesses to describe what he had seen in an investigation of the condition of the unemployed that had taken him to more than twenty states in four months. He described miners in the Mississippi Valley "suffering from the lack of decent necessities of life, [while] food and raw materials were rotting or were destroyed by the millions of tons." He told of women searching for edible scraps in the refuse piles of the markets in Seattle and of wheatfields unharvested in Montana